Developmental trends in the facilitation of multisensory objects with distractors - Downing, Harriet C.; Barutchu, Ayla; Crewther, Sheila G. (Frontiers in Psychology, 2015)
Sensory integration and the ability to discriminate target objects from distractors are critical to survival, yet the developmental trajectories of these abilities are unknown. This study investigated developmental changes in 9- (n=18) and 11-year-old (n=20) children, adolescents (n=19) and adults (n=22) using an audiovisual object discrimination task with uni- and multisensory distractors. Reaction times (RTs) were slower with visual/audiovisual distractors, and although all groups demonstrated facilitation of multisensory RTs in these conditions, children’s and adolescents’ responses corresponded to fewer race model violations than adults’, suggesting protracted maturation of multisensory processes. Multisensory facilitation could not be explained by changes in RT variability, suggesting that tests of race model violations may still have theoretical value at least for familiar multisensory stimuli.